Gene trap and gene inversion methods for conditional gene inactivation in the mouse - Xin, Hong-Bo (Oxford University Press, 2005)
Conditional inactivation of individual genes in mice using site-specific recombinases is an extremely powerful method for determining the complex roles of mammalian genes in developmental and tissue-specific contexts, a major goal of post-genomic research. However, the process of generating mice with recombinase recognition sequences placed at specific locations within a gene, while maintaining a functional allele, is time consuming, expensive and technically challenging. We describe a system that combines gene trap and site-specific DNA inversion to generate mouse embryonic stem (ES) cell clones for the rapid production of conditional knockout mice, and the use of this system in an initial gene trap screen. Gene trapping should allow the selection of thousands of ES cell clones with defined insertions that can be used to generate conditional knockout mice, thereby providing extensive parallelism that eliminates the time-consuming steps of targeting vector construction and homologous recombination for each gene.